Kinematic analysis of the take-off and start of the early flight phase on a large hill (HS-134 m) during the 2009 Nordic World Ski Championships - Janura, M.; Cabell, L.; Svoboda, Z.; Elfmark, M.; Zahalka, F. (Journal of Human Kinetics, 2011)
The take-off is often considered the most significant and difficult phase of a ski jump. Thus, the purpose of this study was to compare three groups of ski jumpers representing different skill levels during the execution of the take-off and start of the early flight phase in ski jumping. A total of 30 athletes, recruited from competitors performing ski jumps on an HS-134 m jumping hill, were categorized into three groups based on jump-length execution. Two-dimensional (2-D) kinematic data were collected from the lower extremities, trunk, and skis of the ski jumpers. Findings indicated that the ski jumpers with shorter jump length demonstrated significantly smaller in-run velocity (p < .05), while the elite and mediocre level ski jumpers exhibited a significantly faster shift of the thigh at the transition from take-off into the early flight of the jump (p < .05) than did the low-level ski jumpers. In addition, the centre of body mass (CoM) of the elite group shifted significantly more forward over the skis (p < .01) than did that of the other two groups. Finally, interindividual differences existed among ski jumpers at similar performance levels. The largest coefficients of variation (CVs) were found for the position changes of the trunk and shank behind the jumping hill edge.